Simulation of bright-dark soliton solutions of the Lonngren wave equation arising the model of transmission lines - Yokus, Asif (World Scientific Publ Co Pte Ltd, 2021)
In this study, the auxiliary equation method is applied successfully to the Lonngren wave equation. Bright soliton, bright-dark soliton solutions are produced, which play an important role in the distribution and distribution of electric charge. In the conclusion and discussion section, the effect of nonlinearity term on wave behavior in bright soliton traveling wave solution is examined. The advantages and disadvantages of the method are discussed. While graphs representing the stationary wave are obtained, special values are given to the constants in the solutions. These graphs are presented as 3D, 2D and contour.
Keywords: The Lonngren wave equation; auxiliary equation method; bright-dark soliton solution